PENGARUH OVERINVESTMENT YANG DIMODERASI OLEH KEBIJAKAN DIVIDEN PADA SEKTOR ENERGI DI INDONESIA - Josua Martua Sitorus; Ahmad Muslim; Maria C. Widiastuti (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine and analyze the impact of overinvestment, liquidity, and Corporate Social Responsibility (CSR) moderated by dividend policy on the company's financial performance. This research was conducted with a quantitative approach. The data used in this study are secondary data sourced from the annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2022 period. The research sample was selected using purposive sampling method so that 22 companies were sampled with 132 observations. The data analysis technique used to test the hypothesis is panel data analysis using the Eviews 12 program. The results showed that overinvestment had no effect on company performance calculated using Basic Earning Point (BEP). Liquidity and CSR partially have a positive and significant effect on company performance. Dividend policy does not moderate the relationship between overinvestment and firm performance. Control variables consisting of company size and business risk partially have a positive and significant effect on company performance. The results of the study inform that the management of energy sector companies needs to increase liquidity and conduct CSR activities actively to improve company performance.